(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article discusses the importance of cooperation at both national and international levels in the development of parasports and examines the relations, memorandums, and agreements implemented to date. It also substantiates that mutually beneficial cooperation between Uzbekistan and the international community is an important process in the practical and theoretical improvement of the Paralympic movement and parasports.